Evolution of the security concept. From the local to the global - Fernández Ferreira, Enrique Eduardo (Cuadernos de Gobierno y Administración Pública, 2019)
The main organizations focused on the analysis of the concept of security, have made clear its evolutionary nature and the need to adapt it to the transformations that occurred with the growing globalization. The necessary integration, defined in the successive Security Strategies adopted at the international and national levels, requires taking into consideration the local perspective, making it a participant in the objectives set at the different levels and Strategies. Our contribution, wants to emphasize the need to deepen internal security, which, without disassociating it from global risks and threats, requires updating, in-depth reflection on the safety of people, those who live in the urban concentrations that make up the whole of the State.
Keywords: United Nations, European Union, human security, security strategies, local security.